Malaysian Islamic Humanitarian Actor: A Case of Global Peace Mission Malaysia (GPM) - Mhd Omar, Mohd Faridh Hafez; Syed Ismail, Sharifah Hayaati (Online Journal of Research in Islamic Studies, 2020)
This paper provides insights into Islamic Humanitarianism in Malaysia with the aim of analyzing the impact of Global Peace Mission Malaysia (GPM) as Islamic Humanitarian actor in providing diverse forms of aid. By using qualitative approaches of journal articles and official reports from media and websites, this paper therefore is aimed to address the first theme of this conference. It begins with definitions of Islamic Humanitarian concept with focus on the three types of humanitarian approaches in the form charity which comprises of zakat, sadaqah and waqf. Then, if offers a brief overview in regards of Malaysia and Islamic humanitarianism and how it has been progressing since the time of first’s Prime Minister until the Pakatan Harapan forms a new government of Malaysia recently. Finally, the paper turns to focus on the role of GPM partnering in new initiative work, leading international commission, and leading in impactful and sustainable projects, providing humanitarian aid training to volunteer and advising government. The four criterions (4 criterions) described the visibility of GPM in providing humanitarian assistance for the needy countries that has made GPM a leading Islamic Humanitarian NGO from Malaysia was is further discussed and defined. This paper concluded that the notion of Islam and the Ummah spirit are the driving force of the cause and funds and leadership are the continuous challenges in humanitarianism.